Prevalence of acute kidney injury in intensive care units: The “COrte de prevalencia de disFunción RenAl y DEpuración en críticos” point-prevalence multicenter study - Herrera-Gutiérrez, Manuel Enrique; Seller Pérez, Gemma Luisa; Sánchez Izquierdo Riera, José Ángel; Maynar Moliner, Javier (Elsevier, 2013)
Purpose: This study aimed to measure the point prevalence of kidney dysfunction (KD) in the intensive care setting. Materials and methods: A point-prevalence, single-day, prospective study was conducted. Of 919 patients present in 42 Intensive care units (ICUs) for 2 specific days (September 2009 and March 2010), 832 cases were included. Mild KD was defined as a measured creatinine clearance of 90 to 60 mL min(-1) 1.73 m(-2), and severe KD was defined as a creatinine clearance less than 60 mL min(-1) 1.73 m(-2). Results: Prevalence of mild KD was 15.9/100 patients/d (13.5-18.5), and severe KD was 42.4/100 patients/d (39.1-45.8). We considered as having a low probability of experiencing KD those patients without chronic kidney disease, acute kidney injury network stage 0, and a serum creatinine less than 1.2 mg/dL, but among them (557 patients), 18.1% (15.2%-21.6%) had mild KD and 24.2% (20.9%-28%) had severe KD. ICU mortality was 10.6% (7.81%-14.4%) for patients without dysfunction, 16.6% (11.2%-24%) for patients with mild KD, and 29.7% (25.2%-34.7%; P<.001) for patients with severe KD, with a relative risk for severe KD vs no KD of 2.54 (1.90-3.40). In 54.3% patients, at least 1 renal insult was reported. One nephrotoxic drug was administered to 34.4% and 2 or more to 14.9% patients, with a lower frequency among those with chronic kidney disease (30.6% vs 50.8%; P<.05). Conclusions: Each day of study, more that half of the patients admitted to the ICU showed some derangement in kidney function. More than 25% of patients not fulfilling the KD criteria by serum creatinine or acute kidney injury network showed, in fact, a severe KD, and this finding was associated with higher mortality. More than 50% of the patients admitted to the ICU were subjected to at least 1 renal insult.
https://openpolicyfinder.jisc.ac.uk/id/publication/4780
Keywords: Insuficiencia renal aguda; Riñones - Enfermedades; Creatinine clearance; Kidney injury acute; Intensive care units